Common genetic variants associated with open-angle glaucoma - Ramdas, Wishal D.; Van Koolwijk, Leonieke M. E.; Lemij, Hans G.; Pasutto, Francesca; Cree, Angela J.; Thorleifsson, Gudmar; Janssen, Sarah F.; Jacoline, Ten Brink; Amin, Najaf; Rivadeneira, Fernando; Wolfs, Roger C. W.; Walters, G. Bragi; et al. (Human Molecular Genetics, 2011)
Open-angle glaucoma (glaucoma) is a major eye disorder characterized by optic disc pathology. Recent genome-wide association studies identified new loci associated with clinically relevant optic disc parameters, such as the optic disc area and vertical cup-disc ratio (VCDR). We examined to what extent these loci are involved in glaucoma. The loci studied include ATOH7, CDC7/TGFBR3 and SALL1 for optic disc area, and CDKN2B, SIX1, SCYL1/LTBP3, CHEK2, ATOH7 and DCLK1 for VCDR. We performed a meta-analysis using data from six independent studies including: the Rotterdam Study (n= 5736), Genetic Research in Isolated Populations combined with Erasmus Rucphen Family study (n= 1750), Amsterdam Glaucoma Study (n= 296) and cohorts from Erlangen and Tübingen (n= 1363), Southampton (n= 702) and deCODE (n= 36 151) resulting in a total of 3161 glaucoma cases and 42 837 controls. Of the eight loci, we found significant evidence (P= 1.41 × 10(-8)) for the association of CDKN2B with glaucoma [odds ratio (OR) for those homozygous for the risk allele: 0.76; 95% confidence interval (CI): 0.70-0.84], for the role of ATOH7 (OR: 1.28; 95% CI: 1.12-1.47) and for SIX1 (OR: 1.20; 95% CI: 1.10-1.31) when adjusting for the number of tested loci. Furthermore, there was a borderline significant association of CDC7/TGFBR3 and SALL1 (both P= 0.04) with glaucoma. In conclusion, we found consistent evidence for three common variants (CDKN2B, ATOH7 and SIX1) significantly associated with glaucoma. These findings may shed new light on the pathophysiological protein pathways leading to glaucoma, and point to pathways involved in the growth and development of the optic nerve.
EVALuna2:9086